Intercultural performativity in learning and interpreting Shakespearean plays:Towards a new model for learning literature. - Abdullah, Nurul Farhana Low (Universiti Sains Malaysia, 2014)

(untitled)
This research investigates the effectiveness of intercultural performance activities on the study of English literature. Its primary objective is to introduce a new approach to teaching Shakespearean drama in the second/foreign language classroom by incorporating elements of traditional theatre.